Research Progress on the Role of the Interaction Between Chronic Inflammation and Fibrosis in Diabetic Nephropathy - XU Jin; LI Jianxing; LIU Zhenhua; ZHANG Xinli (Xiehe Yixue Zazhi)
Diabetic nephropathy (DN), a primary cause of end-stage renal disease (ESRD) in diabetic patients, is pathologically characterized by chronic inflammation and renal fibrosis. Chronic inflammation promotes renal cellular damage, epithelial-mesenchymal transition, and extracellular matrix (ECM) accumulation through mechanisms including immune cell activation, pro-inflammatory cytokine secretion, and initiation of multiple signaling pathways. Excessive ECM deposition disrupts renal architecture and drives tubulointerstitial expansion, thereby accelerating renal functional decline. Recent studies demonstrate that chronic inflammation and fibrosis synergistically propagate DN progression via bidirectional crosstalk. Inflammation serves as an early driver of fibrogenesis and further amplifies fibrotic processes through positive feedback mechanisms, establishing a self-perpetuating inflammation-fibrosis vicious cycle. However, the precise molecular interplay between chronic inflammation and fibrosis remains incompletely elucidated. Thus, in-depth exploration of their interaction mechanisms is crucial for developing novel DN interventions. This review delineates the pathogenic roles of chronic inflammation and fibrosis in DN to advance mechanistic understanding and provide foundational insights for designing innovative therapeutic strategies.